LITERASI MATEMATIS YANG DIKAJI DARI KEMAMPUAN REPRESENTASI DALAM MATERI EKSPRESI ALJABAR SISWA SMP - Susanto, Hermawan; Sugiatno, Sugiatno; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to explain the mathematical literacy of junior high school students in Academic Year 2015/2016, in solving problems related to algebraic expressions in terms of iconic and symbolic representation. This research used descriptive method which applied Case Study form. The subjects of this research were 41 students of SMP Kristen Immanuel Pontianak. The results of data analysis showed that the formulate process of mathematical situations when changing the form of iconic representation, students looked better in making schemes from real situations to pictorial forms (tables). Considering from the formulate process of mathematical situations when changing the form of symbolic representation, students had difficulty in conducting manipulation by using symbols from real situations into symbolic forms. Considering from the process of using iconic representation in accomplishing mathematical literacy questions, the majority of students were able to accomplish mathematical literacy questions which were given by using table representation. Considering from the process of using symbolic representation in accomplishing mathematical literacy problems, upper level students tend to be able to accomplish the questions well. Conversely, middle level students experienced problems in calculation process.Â Â Keywords: Agebraic Expressions, Mathematical Literacy, Representations.